Oil prices and bank credit risk in MENA countries after the 2008 financial crisis. Issue 2 (3rd February 2020) - Wang, Rui; Luo, Hang (Robin)
Abstract : Purpose: The purpose of this paper is to investigate the oil price–bank risk nexus by considering the heterogeneity of bank characters. Design/methodology/approach: This paper empirically tests the effect of oil price movements on bank credit risk by using a sample of 279 banks in the Middle East and North Africa countries from 2011 to 2017. Findings: Authors find robust evidence that the credit risk of bank loan portfolios is negatively associated with increased oil prices. The heterogeneity analysis indicates that the effect of asset quality improvement brought about by rising oil prices is more salient in conventional banks, and banks with small size, low liquidity and whose funding source relies on customers' deposits. Practical implications: The results favor the diversification of bank funding sources, the improvement of a country's financial development, the adoption of explicit deposit insurance and macroprudential policies, such as countercyclical liquidity buffers, to weaken the adverse impact of oil prices declines. Originality/value: The present paper enriches the literature of oil price–bank risk nexus by analyzing the heterogeneity of bank characters and advances our knowledge on the determined factors of bank riskiness and vulnerability.